The Influence of Zumba Exercise on Increasing Fitness, Reducing Body Fat and Body Mass Index in Health Service Employees, Population Control and Family Planning in Madiun City - Wahyuni, Retno Dwi; Peristiowati, Yuli; Kusumawati, Prima Dewi (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT Health and fitness are basic needs that humans need and to achieve them requires fun and sustainable physical activity, including Zumba exercise. The results of tests and measurements in 2021 and 2022, from 119 employees, show that good fitness results remain at 34%, while body mass index and body fat in the normal category have decreased In general, the aim of this research is to determine the impact that Zumba exercise has on increasing fitness, body fat and body mass index. The population in this study were Madiun City PPKB Health Service employees with age requirements of 25-40 and not suffering from heart disease, hypertension and fractures with a total sample of 30 for the zumba exercise group and 30 for the control group. The research design uses One Group Pretest-Posttest Design, One group for the zumba exercise experiment and research was carried out for 4 months, with one workout a week. The data processed in this research is pre-test and post-test data to determine how much improvement the research program has implemented. The data that has been processed shows that there is a significant increase in fitness, namely the VO2max value (2-tailed p = 0,000), for body mass index there was also a significant decrease (2-tailed p = 0,000), and there was also a decrease in body fat percentage (2-tailed p = 0,000) . Zumba exercise can be used as a core or alternative exercise method to increase fitness decreased Body Fat Percentage and Body Mass Index. Keywords: Zumba Exercise, Fitness, Body Fat, Body Mass Index, Madiun City Health Office  ABSTRAK Kesehatan dan kebugaran adalah kebutuhan dasar yang dibutuhkan manusia dan untuk mencapainya membutuhkan aktivitas fisik yang menyenangkan dan berkelanjutan diantaranya senam zumba. Hasil tes dan pengukuran pada tahun 2021 dan 2022 dari 119 pegawai Dinas Kesehatan PP KB Kota Madiun menunjukkan hasil kebugaran baik tetap sebesar 34%, sedangkan indeks massa tubuh dan lemak tubuh pada kategori normal mengalami penurunan. Secara umum tujuan dari penelitian ini adalah untuk mengetahui dampak yang diberikan oleh senam zumba terhadap peningkatan kebugaran, Bodyfat dan Indeks Massa Tubuh. Populasi dalam penelitian ini adalah Pegawai Dinas Kesehatan PPKB Kota Madiun dengan syarat usia 25-40 serta tidak menderita jantung, hipertensi dan fraktur dengan total sampel 30 untuk kelompok senam zumba dan 30 kelompok kontrol. Desain penelitian menggunakan One Group Prestest-Postest Design. Satu kelompok menggunakan eksperimen dengan senam zumba dan penelitian dilakukan selama 4 bulan, dengan satu kali latihan dalam seminggu. Data yang diolah pada penelitian ini adalah data pre-test dan post-test untuk mengetahui seberapa besar peningkatan dari program penelitian yang telah dilaksanakan. Dari data yang telah diolah menunjukkan bahwa pada kelompok ekperimen terdapat peningkatan yang signifikan terhadap kebugaran yaitu nilai VO2max (2-tailed p = 0,000), untuk indeks massa tubuh pun terjadi penurunan yang signifikan (2-tailed p = 0,00), dan terjadi penurunan juga pada persentase lemak tubuh (2-tailed p = 0,000). Senam zumba dapat dijadikan metode latihan inti maupun selingan untuk meningkatkan kebugaran, dan menurunkan prosentase lemak tubuh dan Indeks Massa Tubuh. Kata Kunci: Senam Zumba, Kebugaran, Bodyfat, Indeks Masa Tubuh, Dinkes PPKB Kota Madiun